A Defense of Kohut's "Self". Issue 1 (2nd January 2021) - Baker, August
ABSTRACT: Stolorow and Atwood have repetitively and insistently criticized Kohut's theoretical language, saying that the noun "self" is a reification that negates contextual embeddedness. This essay shows that selves are not things: they just shatter like them. Nouns are just words: they cannot reify. Kohut's self presupposes—not opposes—the authors' Experiential Selfhood. Embeddedness presupposes—not opposes—a self.